Eucalyptus grandis Response to Calcium Fertilization in Colombia - Zach S Grover; Rachel L Cook; Marcela Zapata; J Byron Urrego; Timothy J Albaugh; Ariel Zelaya; Tomasz Ozyhar; Rafael Rubilar; David R Carter; Otávio C Campoe (Forest Science, 2021)
Calcium (Ca) is a critical plant nutrient typically applied at the time of planting in intensive Eucalyptus plantations in South America. At two sites in Colombia, we examined (1) calcium source by comparing growth after application of 100 kg ha−1 elemental Ca as lime or as pelletized highly reactive calcium fertilizer (HRCF) compared to a no application control, and (2) Ca rate by applying 0, 100, 200, and 400 kg ha−1 elemental Ca as HRCF with the addition of nitrogen, phosphorus, potassium, sulfur, and boron (NPKSB). We assessed height, diameter, and volume after 12 and 24 months. There were no growth differences from Ca source at the 100 kg ha−1 rate. We found increased volume after 24 months at the “Popayan” site with 200 and 400 kg ha−1 Ca HRCF+NPKSB treatments (112 and 113 m3 ha−1, respectively) compared to control (92 m3 ha−1), a 22% increase. In contrast, volume did not differ after 24 months at the “Darien” site, ranging from 114 m3 ha−1 in the 0 kg ha−1 Ca HRCF+NPKSB treatment to 98 m3 ha−1 in the control. Differences in response are likely due to soil characteristics, such as organic matter, emphasizing the importance of identifying site-specific nutrient deficiencies.